Glucuronoxylan-mediated silver nanoparticles: green synthesis, antimicrobial and wound healing applications. Issue 68 (5th September 2017) - Muhammad, Gulzar; Hussain, Muhammad Ajaz; Amin, Muhammad; Hussain, Syed Zajif; Hussain, Irshad; Abbas Bukhari, Syed Nasir; Naeem-ul-Hassan, Muhammad
Abstract : Hydrogel forming polysaccharides are attracting attention for the design of diverse nature silver nanoparticles (Ag NPs) with potential biological applications. Abstract : Hydrogel forming polysaccharides are attracting attention for the design of diverse nature silver nanoparticles (Ag NPs) with potential biological applications. Herein, we report the green synthesis of Ag NPs and their antimicrobial activity along with their potential application in wound dressings. Glucuronoxylan (GX) isolated from seeds of Mimosa pudica (MP) was used as a stabilizing/capping agent to prepare the NPs under diffused sunlight using different concentrations of AgNO3 . The progress of the reaction was monitored using a UV-visible spectrophotometer and characteristic surface plasmon absorption (SPR) bands were found in the range of 390–465 nm. The morphology and elemental composition of the synthesized Ag NPs were analyzed using scanning electron microscopy equipped with STEM and EDS detectors and the diameter of the Ag NPs was found to be in the range of 2 to 18 nm. The synthesized NPs exhibited antimicrobial potential against Staphylococcus epidermidis, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Staphylococcus aureus, Aspergillus niger, Penicillium notatum, Rhizopus stolonifer and Actinomycetes odontolyticus . The minimal inhibitory concentrations (MICs) of the Ag NPs against different pathogenic strains were determined. Moreover, the dressing prepared from Ag NP impregnated GX exhibited a remarkable wound healing potential in rabbits. In situ synthesized Ag NPs were stored in the form of GX thin films and their UV/vis spectra exhibited that the texture of the Ag NPs remained intact after a six month storage period.